ANALYSIS OF INFLUENCING FACTORS MOTIVATING WOMEN TO ENTREPRENEURSHIP THROUGH ONLINE BUSINESS IN CIKARANG - Dian Rachmawati Afandi; Indra Permana; Retno Puspitasari; Fachrial Banyu Asmoro (SEAN Institute, 2022)
In modern and digital times like today, women of course, it is no less competitive than the men. The abundance of natural talents what the women have and their awareness to help improving his family's economy, being one of the factors why Indonesian women pursue the field of entrepreneurship. Development such rapid technology also affects the mindset or women's insights. In this study, researchers aimed to knowing the factors that motivate women in entrepreneurship. Researchers took 100 female entrepreneur respondents as a sample. Data collection is carried out by distributing questionnaires. Research this is a quantitative descriptive study. Research using factor analysis techniques to look for factors that motivate women in entrepreneurship. Analysis using the program SPSS. The results of this research show that there are 5 factors that formed in motivating women in online business entrepreneurship through facebook groups namely; family factors, self-development factors, factors of need to achieve, factors of unemployment or not having unused work and funds factor.